Complications of Laparoscopic Cholecystectomy (Journal of Surgical Sciences, 2019)
Background: laparoscopic cholecystectomy is now regarded as the "Gold Standard" treatment option for benign gallbladder disease. But it is not free of procedure related complications. Objective: To review the complications of laparoscopic cholecystectomy for gall stone disease.Materials & Method: A prospective observational study was carried out over a period of 9 years beginning from 1st of July 2003 till 30th of June 2012 in Comilla Medical College Hospital and several private hospitals of Comilla. A total of 946 patients who underwent laparoscopic cholecystectomy for symptomatic and asymptomatic gallstone disease as confirmed by ultrasound scan were included. Patient having cirrhosis of liver, ischaemic heart disease, suspected carcinoma of gall bladder were excluded from the study. The outcome including the complications was analyzed.Result: Out of 946 patients 632 (66.80%) were females and 314 (33.19%) were males. Most (92.3%) of them were between 21-50 years of age. The commonest immediate complication was bleeding from liver bed (9.40%), from vascular injury in Callot's triangle (5.17%) and from the trocar site (4%). There was spillage of gallstones in 104(10.99%) cases. Bowel injury was seen in only one (0.10%) case. Bile leakage was observed in 4(.42%) cases that also include CBD injury .in 3 cases. The procedure was converted to open surgery in 11(1.17%) cases. Port site infection was seen in 43 (4.54%) cases. Late complications include port site hernia in 6 (0.63%) cases, port site keloid in 1 (.1%) case and CBD stricture in 5 (0.54%) cases. Mortality was unavoidable in in 2(0.21%) cases.Conclusion: With increasing experience laparoscopic cholecystectomy can be a safe and effective procedure for most patients with cholelithiasis. Proper training and sound knowledge of possible complications can yield favorable results and lesser complications.Journal of Surgical Sciences (2013) Vol. 17 (2) :73-79